1974
DOI: 10.1083/jcb.60.2.356
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle-Specific Changes in Histone Phosphorylation Associated With Cell Proliferation and Chromosome Condensation

Abstract: Preparative polyacrylamide gel electrophoresis was used to examine histone phosphorylation in synchronized Chinese hamster cells (line CHO) . Results showed that histone fl phosphorylation, absent in GI-arrested and early GI-traversing cells, commences 2 h before entry of traversing cells into the S phase . It is concluded that fl phosphorylation is one of the earliest biochemical events associated with conversion of nonproliferating cells to proliferating cells occurring on old fi before synthesis of new fl d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
65
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(69 citation statements)
references
References 35 publications
3
65
0
Order By: Relevance
“…15) and pHH3 (G 2 -M phase; ref. 16), as two additional transit compartments downstream of p-Rb. As p-Rb can also be used as a phenotypic biomarker for late G 1 -phase (6,7), this extended PD model can be regarded as a simplified integrated cell-cycle model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15) and pHH3 (G 2 -M phase; ref. 16), as two additional transit compartments downstream of p-Rb. As p-Rb can also be used as a phenotypic biomarker for late G 1 -phase (6,7), this extended PD model can be regarded as a simplified integrated cell-cycle model.…”
Section: Discussionmentioning
confidence: 99%
“…1) was developed using colo-205 xenograft tumor data and is composed of four transit compartments, each corresponding to early G 1 , late G 1 , S, and G 2 -M cell-cycle phases in a sequential, open-loop manner. The biomarkers, p-Rb, TopoIIa, and pHH3, were used to represent the change in cell phase density in late G 1 , S, and G 2 -M phases, respectively (6,7,15,16). As the formation of p-Rb occurs at the G 1 restriction point, the drug effect was implemented on the transition between early and late G 1 -phase.…”
Section: Translational Relevancementioning
confidence: 99%
“…In CHO cells both histones Hi and H3 become rapidly phosphorylated at the time cells cross the G2/M boundary of the cell cycle (13,14). Histone phosphorylation is thought to be involved in either the mechanism which triggers the chromosomes to condense or the maintenance of the mitotic chromatin in the condensed form.…”
Section: Discussionmentioning
confidence: 99%
“…In higher eucaryotes and also in the slime mold Physarum polycephalum, the phosphorylation of histone H3 and histone Hi is associated with the condensation of chromatin during mitosis (3,7,13,14). The apparent phosphorylation of Achlya histones during heat shock was therefore of particular interest to us, since Achlya nuclei normally contain no discernible heterochromatin and Achlya chromosomes like those of the related water mold Saprolegnia ferax (15) are not thought to condense even when cells are undergoing mitosis.…”
mentioning
confidence: 99%
“…Condensation of the interphase chromosome into mitotic chromosome involved two specific phosphorylation events (Gurley et al 1974) in synchronised chinese hamster cell cul ture. It was observed that subfraction of HI and histone of H3 (Arginine-rich) were rapidly phosphorylated when cells were passing through G2/M boundary and going to prophase.…”
mentioning
confidence: 99%